Individual Differences Among Children in Sucrose Detection Thresholds - Paule V. Joseph; Danielle R. Reed; Julie A. Mennella (2015)
Little research has focused on whether there are individual differences among children in their sensitivity to sweet taste and, if so, the biological correlates of such differences.